Bigfoot Swims in the Garden of Eden: A History of Hellbenders and American Cultural Identity - Craig, Andrew (Humanimalia, 2024)
Encounters with hellbenders, an aquatic salamander found throughout the Appalachian Mountain range, has inspired Americans to reimagine their relationship with nature since the colonial period. These salamanders spend the majority of their time curled up in the nests they build under rocks on the bottom of cool, fast flowing streams. There, hellbenders blend into their surroundings and are commonly out of human sight. Only rarely do humans see hellbenders. According to written and oral accounts, hellbenders are generally only seen by humans when they bite angler’s bait. This essay examines human accounts of encounters with hellbenders from the eighteenth century through the twenty-first century. It argues that since the colonial period, Americans utilized encounters with hellbenders to reexamine their relationship with nature. This essay draws from the literary and historical analysis of scholars who have studied Bigfoot myths to argue that hellbenders have functioned rhetorically in the same way as Bigfoot myths, serving as a totem that helps Americans connect to an imagined wild environment. As these accounts demonstrate, human encounters with seemingly exotic, and commonly unseen, non-human animals like hellbenders have played a key role in the epistemological process that gave birth to the American wildlife conversation movement.            This examination of human encounters with hellbenders shows American’s have reimagined their relationship to the environment through encounters with hellbenders over three centuries. In the eighteenth century, encounters with hellbenders influenced the creation of the American national identity after the United States formally severed their ties to Europe and founded a new nation. From the nineteenth century onward, American men developed a conversation movement around the idea of protecting so-called wild spaces and seemingly exotic animals like hellbenders to reenforce the American identity and their masculinity.